Supporting motivation in teams working remotely: The role of basic psychological needs. (2nd July 2020) - Orsini, Cesar; Rodrigues, Veena
Abstract: The current disruptive and abrupt transition to remote activities that educational institutions are facing represents a major challenge for the entire academic community. While most concerns have centred on how learning activities may successfully transit from face-to-face to remote delivery, little attention has been given to how educators can be supported in this new unchartered territory. In this article, we discuss the crucial role of team leaders and how their management and leadership style may have great potential to support educators' motivation. Based on Self-determination Theory, we offer a framework through which team leaders may contribute to create optimal remote working environments for educators. We argue that educators' autonomous motivation depends on how they perceive their remote work environment as supportive of their basic psychological needs of autonomy, competence and relatedness. Then, we highlight a series of practical recommendations by which team leaders may be more needs-supportive. Working from home requires space, trust, open communication and flexibility, especially considering that team members may have different clinical or personal circumstances. We therefore hope these suggestions are helpful to cultivate educators' autonomous motivation, which is beneficial not only for themselves but also for others in their institution, including their co-workers and students.